Legalitas Pencatatan Perkawinan Pasangan Mualaf dari Perkawinan Adat Dayak Meratus dalam Sistem Hukum Indonesia: Analisis Kritis terhadap Putusan Nomor: 262/Pdt.P/2024/PA.Kdg, Nomor 253/Pdt.P/2024/PA.Kdg dan Nomor: 201/Pdt.P/2025/PA.Kdg - Gusti Muhamad Shadiq; Zulfa Jamalie; Anwar Hafidzi (Himpunan Ilmu Hukum dan Ilmu Hukum Islam, 2026)
Marriage in Indonesia requires both religious validity and state registration, creating legal challenges for Dayak Meratus customary marriages that lack formal recognition. These issues intensify when couples convert to Islam, necessitating legal alignment with Islamic and state systems. This study uses a normativeempirical juridical approach, examining regulations and Religious Court decisions. It finds that although itsbat nikah provides a legal pathway, administrative barriers, particularly within SIMKAH, limit effective registration. This results in tensions between customary, Islamic and state law, affecting legal protection. The study emphasizes the need for inclusive legal pluralism, institutional coordination, and administrative reform to ensure legal certainty and protect indigenous civil rights.